Cardiac magnetic resonance for ischaemia and viability detection. Guiding patient selection to revascularization in coronary chronic total occlusions: The CARISMA_CTO study design. (1st December 2018) - Pica, S.; Di Giovine, G.; Bollati, M.; Testa, L.; Bedogni, F.; Camporeale, A.; Pontone, G.; Andreini, D.; Monti, L.; Gasparini, G.; Grancini, L.; Secco, G.G.; et al.
Abstract: Background: It is debated whether percutaneous revascularization (PCI) of total coronary chronic occlusion (CTO) is superior to optimal medical therapy (OMT) in improving symptoms, left ventricular (LV) function and major adverse cardiac/cerebrovascular events (MACCE). Furthermore, CTO-PCI is a challenging technique, with lower success rate than in other settings. A systematic analysis of baseline LV function, infarction extent and ischaemic burden to predict response to revascularization has never been performed. Purposes: To establish a CMR protocol to identify patients (pts) who can benefit most from CTO-PCI. Myocardial viability/ischaemia retains high biological plausibility as predictors of response to revascularization. Therefore, baseline viability (necrotic tissue extent, response to inotropic stimulation) and ischaemia (perfusion defect, wall motion abnormality during stress) will be studied as potential predictors of mechanical LV segmental improvement and ischaemic burden reduction in CTO territory (primary endpoint), LV remodelling and global function, Seattle Angina Questionnaire, and MACCE improvement (secondary endpoints) in the follow-up. Methods: Pts with CTO suitable for PCI undergo stress-CMR for viability/ischaemia assessment. Pts with normal LV function undergo adenosine, those with moderately-reduced ejection fraction (EF) and wall motion abnormalities high-dose dobutamine, pts with EF <35% low-dose dobutamine. All pts undergo late gadolinium enhancement and repeat the same scan at 12 ± 3 months, regardless of PCI success or decision for OMT. Conclusions: A multi-parameter CMR protocol tailored on pts characteristics to study viability/ischaemia could help in identifying responders in terms of LV function, ischaemic burden and clinical outcome among pts suitable for CTO-PCI, improving selection of best candidates to percutaneous revascularization. Highlights: CTO-PCI has not demonstrated a clear benefit as compared to optimal medical therapy. This is likely related to lack of proper patient selection and CTO-PCI related complications rate. A Multiparameter CMR assessment of viability/ischaemia will be correlated to mechanical, ischaemic, clinical response to PCI. The study results may help guide clinical management of patients candidate to CTO-PCI, optimizing the risk-to-benefit ratio.